An eye-opening case report of constrictive pericarditis. Issue 7 (25th July 2022) - Dhont, Sebastiaan; Van Belleghem, Yves; De Zaeytijd, Julie; Vandecasteele, Els
Abstract: Background: Constrictive pericarditis is characterized by the encasement of the heart by a stiff pericardium leading to impaired diastolic function, which ultimately leads to congestive heart failure. Case summary: We report a case of a young woman, who first presented to the ophthalmologist with the sudden appearance of floaters and vision reduction. Eventually, invasive haemodynamic assessment led to the diagnosis of constrictive pericarditis leading to venous congestion. Conclusion: Understanding the pathophysiology and integrating the results of invasive and non-invasive diagnostic work up is important in making this challenging diagnosis.